Environmental & architectural phenomenology. Vol. 35, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2024)
The summer-fall 2024 issue of ENVIRONMENTAL & ARCHITECTURAL PHENOMENOLOGY celebrates 35 years of publication and includes the following items: Philosopher Ingrid Leman Stefanovic provides a celebratory commentary on 35 years of EAP. EAP editor David Seamon draws on philosopher Paul Ricoeur’s “hermeneutics of restoration of meaning” as one thematic means to identify EAP’s major aim over the years. Geographer Edward Relph considers artificial intelligence as it might be critiqued via the thinking of philosopher Hannah Arendt and her insights on modernity’s invention of totalitarianism. Philosopher Kenn Maly examines the phenomenon of water via the four qualities of substance, flow, non-duality, and freedom. Chinese geographers Xu Huang and Zichuan Guo offer an ethnographic picture of Chengdu, China’s He-Ming Teahouse, opened in 1923. Artist and writer Vicki King considers how the paintings of Canadian-American abstract-expressionist artist Agnes Martin “evoke sensual memories of New Mexico.”
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals